Neuropsychological assessment for first-episode psychosis patients in low resource settings - Mwesiga, Emmanuel Kiiza (Department of Psychiatry and Mental Health, 2022)
Introduction: Cognitive impairment is the most significant predictor of long-term outcomes in psychotic disorders, and neuropsychological assessment is therefore recommended in first-episode psychosis patients. However, the literature on neuropsychological assessment for first-episode psychosis patients in low resource settings is limited, the clinical utility of such assessments are unclear, and lengthy assessments may not be practicable in these contexts. This thesis therefore investigated 1) which brief neuropsychological assessment measures researched in patients with psychotic disorders from low and middle-income countries are appropriate for cognitive screening, 2) the differences in prevalence and profile of cognitive impairment between first-episode psychosis patients and healthy peers in one low resource setting, 3) the association of clinical variables with impairment in different cognitive domains in first-episode psychosis patients from one low resource setting, and 4) the validity of the NeuroScreen (a collection of brief neuropsychological test delivered via smartphone) for neuropsychological assessment in first-episode psychosis patients in this setting (as determined by comparison with a gold standard evaluation). Methods: First, a systematic review of articles in which brief neuropsychological assessments were researched in patients with psychotic disorders from low and middle-income countries was performed. The 2014 Working Group on Screening and Assessment (WGSA) guidelines were used as a benchmark of the appropriateness for cognitive screening for the neuropsychological assessment measures employed. Second, first-episode psychosis patients and matched healthy peers were recruited into an observational study at the National mental referral hospital in Uganda. Clinical variables were collated (including sociodemographic characteristics, dietary history, previous childhood trauma and illness severity), and after the resolution of psychotic symptoms, a neuropsychological assessment was performed using the gold standard MATRICS consensus cognitive battery. Student t-tests and chi-square tests were used to determine differences in the prevalence and profile of cognitive impairment in patients with psychosis and healthy peers. Multiple linear regression analyses were used to determined associations between clinical variables and cognitive domains while controlling for potential confounders. Finally, Pearson's rank correlation coefficients and receiver operating curves were computed to examine the validity of the NeuroScreen against the MATRICS consensus cognitive battery. Results: In the 29 articles reviewed, none of the neuropsychological measures researched in patients with psychotic disorders of low and middle-income countries was appropriate for cognitive screening according to the Working Group on Screening and Assessment (WGSA) guidelines. Neuropsychological assessment with the MATRICS consensus cognitive battery found the burden of cognitive impairment in first-episode psychosis patients six times that of healthy peers. The largest cognitive impairment burden was in the visual learning and memory domain. Increased age was associated with impairment in the domains of the speed of processing (p= 0.001). . Cassava rich diets had a negative association with cognitive impairment in the visual learning and memory domain (p=0.04). There were no significant associations between sex, history of childhood trauma or illness severity with any of the seven cognitive domains. A composite score from five cognitive domains of the NeuroScreen had a moderate accuracy of 0.79 compared to the MATRICS consensus cognitive battery. Conclusion: There is need for further research on appropriate measures for neuropsychological assessment in low resource settings. As demonstrated here, the use of such assessments may reveal modifiable risk factors for such impairment; appropriate nutrition may be a particularly important intervention for individuals with psychotic disorders in poorly resourced settings. The NeuroScreen may be useful for neuropsychological assessment of patients with psychotic disorders in low resource settings but needs modification to improve its accuracy.